Faktor Yang Memengaruhi Motivasi Kerja Tenaga Kesehatan Di Puskesmas Gunungtua Kecamatan Padang Bolak Kabupaten Padang Lawas Utara - Bintang Simbolon; Ismail Efendy; Indah Anggraini (STIKes Ibnu Sina Ajibarang, 2024)
Motivation is the process of willingness to perform a high level of effort to achieve organizational goals conditioned by the ability of the effort to satisfy some individual needs. Although in general motivation refers to the effort made to achieve each goal. The purpose of the study was to analyze the factors that influence the work motivation of health workers at Gunungtua Health Center, Padang Bolak District, North Padang Lawas Regency. The research design used Analytical Survey method with Cross Sectional approach. The population in this study were all health workers, especially midwives, namely 59 people, all of whom were sampled. Data analysis used univariate analysis, bivariate with chi-square test and multivariate with logistic regression.The results of logistic regression research show that there is an influence of attitude p = 0.001, responsibility p = 0.003, career path p = 0.000 and work environment p = 0.001 on the work motivation of health workers at Gunungtua Health Center, Padang Bolak District, North Padang Lawas Regency, while the dominant factor is career path p = 0.000 and 95% CI = 5,389-316,539 with Exp (B) 41,303.The conclusion of this study is that there is an influence of attitude, responsibility, career path and work environment, while education and leadership have no influence on the work motivation of health workers, the most dominant career path influences the work motivation of health workers at Gunungtua Health Center, Padang Bolak District, North Padang Lawas Regency. It is recommended that the Gunungtua Health Center to increase the work motivation of health workers must be able to prepare, place their health workers in the right work position according to their field and must provide work encouragement and career development for health workers by implementing a planning system and participation in the implementation of promotion activities.